An observational method to code concussions in the National Hockey League (NHL): the heads-up checklist - Hutchison, M. G.; Comper, P.; Meeuwisse, W. H.; Echemendia, R. J. (British Journal of Sports Medicine, 2014)
Background: Development of effective strategies for preventing concussions is a priority in all sports, including ice hockey. Digital video records of sports events contain a rich source of valuable information, and are therefore a promising resource for analysing situational factors and injury mechanisms related to concussion. Aim: To determine whether independent raters reliably agreed on the antecedent events and mechanisms of injury when using a standardised observational tool known as the heads-up checklist (HUC) to code digital video records of concussions in the National Hockey League (NHL). Methods: The study occurred in two phases. In phase 1, four raters (2 naive and 2 expert) independently viewed and completed HUCs for 25 video records of NHL concussions randomly chosen from the pool of concussion events from the 2006-2007 regular season. Following initial analysis, three additional factors were added to the HUC, resulting in a total of 17 factors of interest. Two expert raters then viewed the remaining concussion events from the 2006-2007 season, as well as all digital video records of concussion events up to 31 December 2009 (n=174). Results: For phase 1, the majority of the factors had a value of 0.6 or higher (8 of 15 factors for naïve raters; 11 of 15 factors for expert raters). For phase 2, all the factors had a total percent agreement value greater than 0.8 and ? values of >0.65 for the expert raters. Conclusions: HUC is an objective, reliable tool for coding the antecedent events and mechanisms of concussions in the NHL.